PENGELOLAAN TAMAN BACA MASYARAKAT - Misriyani, Misriyani; Mulyono, Sungkowo Edy (Journal of Nonformal Education and Community Empowerment, 2019)
This study aims to describe management, and determine the supporting and inhibiting factors of TBM Taman Pintar OI Kudus. The research method uses a qualitative approach. The research subjects included the chairman, 2 managers, 3 volunteers and 1 visitor, while the informants included 2 visitors. Data collection techniques using observation, documentation, and interviews. Data analysis uses interactive models according to Miles and Huberman. The technique for checking the validity of data uses the theory, source and method triangulation techniques. The results showed that the management at TBM Taman Pintar OI Kudus was able to run well. Supporting factors include good and adequate facilities, good and adequate teaching and educational staff, support from the community and BPK OI, as well as funds from donors and contributions from BPK OI Kudus members. Inhibiting factors include boredom and laziness of children, as well as various activities that are owned by the managers and volunteers.